Seasonal Fishery Closure in the Northern Bay of Bengal Causes Immediate but Contrasting Ecological and Socioeconomic Impacts - Islam, Mohammad Mahmudul; Begum, Amany; Rahman, Syed Mohammad Aminur; Ullah, Hadayet (Frontiers in Marine Science, 2021)
Bangladesh has introduced a monsoonal fishery closure in the Bay of Bengal to ensure the conservation of fish stocks and productive breeding grounds. While the fishing ban has likely supported this goal, it has also sparked protest and resentment among small-scale fishers. This study investigated fishers’ perceptions of the 65-day fishing ban between May and July in the Bay of Bengal. We collected both qualitative and quantitative data from five coastal fishing communities. Data were analyzed to explore fishers’ perceptions of the socioeconomic and ecological impacts of the closure. While most respondents agreed that the closure produced positive ecological outcomes, they felt that their income and food security had been negatively affected. Importantly, crew members perceived their losses to be more extreme than the boat skipper or owner due to their overreliance on the fishery and lack of alternative skills and occupations. These fishers cannot forfeit their livelihoods and food security needs, as they are already living on the margins of subsistence. This social ramification emphasizes the necessity of understanding the interconnection between fishers’ socioeconomic conditions and conservation needs. Social-ecological trade-offs and inequalities raise the question of social equity and environmental justice, which could ultimately compromise management and conservation effectiveness and legitimacy. The involvement of local communities in the decision-making process for future fishery interventions could enhance both the livelihood opportunities and the positive ecological outcomes in the Bay of Bengal marine ecosystem.